Padrões Internacionais de Conservação da Biodiversidade: certificações florestais e regulação jurídica envolvendo povos e comunidades tradicionais da Amazônia. - Silva, Liana Amin Lima da (2011)
This study aims at establishing a relationship between local and global environmental governance, based on Keohane e Nye (2000), Delmas and Young (2009), Gonçalves and Costa (2011). The focus is on the partnerships established between transnational conservation non-governmental organizations (NGOs) and local organizations of indigenous peoples and traditional communities of the Amazon. By examining the legalization (ABBOTT,et al., 2000; COSTA, 2006), we see how international legal instruments that address multicultural human rights and biodiversity conservation affect the reality of the peoples in the Amazon. Based on Habermas (2008a, 2008b) and on the teachings of Rancière (1996), we perceive the Law as a central category, both by its government and non-government regulations and by it acknowledgement of the custom-based rights of different groups that make up the country’s entire population, in a way that the consensus towards global governance is faced with the dissents, which are inherent to cultural diversity. We have also take up the lessons of Polanyi (2000) with the aim of understanding the relationship between economic and social systems. Concerning sustainable development, this study is based on Boulding (1966), Furtado (1998), Sachs (2002) and Veiga (2010). Corroborating the transdisciplinary nature of this work, we seek to establish a dialogue involving anthopology, especially Sahlins (1997), Bourdieu (2007), Almeida (2008), Cunha (2009), Diegues (2004) and, the Law, Souza Filho (2010) and Shiraishi Neto (2010, 2011). The discussion herein contextualizes the dichotomy between “community and society”, proposed by Tönnies (1947) and Weber (2000), in an attempt to go beyond it. By analyzing specific cases, special attention was given to the implementation of the FairWild Standard, a certification of sustainable wild collection of medicinal and aromatic plants, in Silves (AM), with the following actors being directly involved: International Union for Conservation of Nature (IUCN) and Vida Verde da Amazônia Association (Avive). This study has also looked at other cases of community certification, especially the approach adopted by the Forest Stewardship Council (FSC). The findings point to, in short, the potential of economic mechanisms in biodiversity conservation and in ensuring the rights of traditional societies when they enter the responsible business market, seeking on the implementation of community-based sustainable development.